Comparison between the six-minute walk test and the six-minute step test in post stroke patients - Da Silva, Talita Dias; Raimundo, Rodrigo Daminello; Ferreira, Celso; Torriani-Pasin, Camila; Monteiro, Carlos Bandeira de Mello; Theodoro Júnior, Osmar Aparecido; Valenti, Vitor E [UNESP]; Adami, Fernando; De Oliveira, Eliane Pires; Barnabé, Viviani; De Abreu, Luiz Carlos (Springer Nature, 2013)
Background: The Stroke remains one of the major chronic diseases worldwide, and is considered a major cause of disability, which results not only in persistent neurological deficits, but also in the high physical deconditioning, nevertheless there are not many forms of assessing functional capacity in this population. We aimed to investigate the feasibility of the Six Minute Walk Teste and the Six-Minute Step Test (6MST) in post-stroke patients and compare the behavior of physiological variables during the 6MST and the Six-Minute Walk Test (6MWT), by correlating the functional performance obtained in both tests. Method. The 6MWT was carried out according to the American Thoracic Society (ATS) and the 6MST was performed in six minutes in order to compare it to the 6MWT in a 20 cm step. Was included post-stroke individuals able to walk without aid. All of them did the 6MWT and the 6MST. Results: 12 patients participated in the study. There was no statistical difference in the parameters analyzed when tests were compared. There was poor correlation between the functional performance in both tests. Conclusion: The 6MWT and the 6MST is feasible for post-stroke patients and physiological responses are equal during the performance of both tests. However, there was no correlation with respect to functional performance, which was assessed by the distance walked in the 6MWT and by the number of steps climbed in the 6MST. © 2013 da Silva et al.; licensee BioMed Central Ltd.
Keywords: Exercise test; Mobility limitation; Stroke; adult; body equilibrium; cerebrovascular accident; clinical article; diastolic blood pressure; exercise; female; heart rate; human; male; motor performance; oxygen saturation; six minute step test; Six Minute Walk Test; walking